Perbezaan gaya pembelajaran antara generasi-x dan generasi boom terhadap latihan - Florence, Tampang (University Malaysia Sarawak, UNIMAS., 2003)
The purpose ofthis study is to identifY the learning styles differences between Generation-X and Generation-Boom in ICV training. There are 3 factors involved in training such as training methods, training environments and training contents that preferred by these two generations. Questionnaire was used in this study to get the necessary data. There are 64 respondents chosen from these two generations where by 17 respondents from Generation-X and 47 respondents from Generation-Boom. The statistical method used to analyze this study was crosstabs descriptive analysis to see the differences between these two generations in training. Results showed that there is a difference between these two generations in learning styles preferences as well as in training method and training contents. However, there is no difference between Generation-X and Generation-Boom in training environment preferences. So, it is a good idea if the organization can identifY the employee's learning styles because it affects the effectiveness and transfer oftraining.